2016
DOI: 10.7439/ijbar.v7i6.3366
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological profile and sensitivity pattern of microorganisms causing Urinary Tract Infection at a tertiary care center in eastern Uttar Pradesh

Abstract: Introduction: Urinary tract infection (UTI) is one of the most common infections worldwide and the pattern of antimicrobial susceptibility varies widely in different geographical regions depending on the antibiotic policies. Aim: To know the bacteriological profile of UTIs and the antibiogram of uropathogens in eastern Uttar Pradesh. Material and Methods: This study was prospective and conducted at tertiary care center in one year study duration (2015). All the patients clinically suspected of having UTI were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
5
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 18 publications
(17 reference statements)
5
5
2
Order By: Relevance
“…45.8% of samples showed growth of various pathogens in our study which is similar to Ruchi Mishra et al, 43.6%. 9 Positivity of females in our study was 71.4% which is similar to the study conducted by Latika Jshch et al, 77.40%. 10 61.2% of positive samples in our study were of the age group 21-40 years, similar to Shamataj Kattalagere Razak et al, 11 Gram negative organisms predominated in our study in comparison to gram positive organisms, which is similar to other studies.…”
Section: Resultssupporting
confidence: 91%
“…45.8% of samples showed growth of various pathogens in our study which is similar to Ruchi Mishra et al, 43.6%. 9 Positivity of females in our study was 71.4% which is similar to the study conducted by Latika Jshch et al, 77.40%. 10 61.2% of positive samples in our study were of the age group 21-40 years, similar to Shamataj Kattalagere Razak et al, 11 Gram negative organisms predominated in our study in comparison to gram positive organisms, which is similar to other studies.…”
Section: Resultssupporting
confidence: 91%
“…Study by Hamdan et al, (2015) in Sudan shows that there is no association between pyuria and prevalence of UTI. Studies by Mishra et al, 9 , Akram et al, 16 and Jennifer et al, 10 revealed the involvement of Gram negative enteric organisms that commonly causes urinary tract infections, such as E. coli, the Klebsiella species, and the Proteus species similarly, the predominant number of pathogens isolated in our study were also Gram negative bacilli (Table 4). …”
Section: Resultsmentioning
confidence: 58%
“…Whereas only dysuria is the predominant symptom in Mishra et al, 9 and Jennifer et al, 10 study groups.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations